Mathematical and Grammatical Error Analysis in Local Wisdom-Based Problem-Solving Construction - Fauziyah, Mailulah Ely; Tahmida, Nova Shufia; Cahyanita, Elvin (Jurnal Gentala Pendidikan Dasar, 2026)
The quality of mathematical problem construction plays a crucial role in supporting meaningful problem-solving learning. However, errors in both mathematical reasoning and grammatical structure are still frequently found in problems designed by prospective teachers. This research focuses on analyzing the patterns of mathematical and grammatical errors in problem-solving tasks based on local wisdom constructed by prospective elementary school teachers. A qualitative research design based on document analysis was employed in this study. The data consisted of 225 essay-type problems created by 45 students in a mathematics problem-solving course. Data were analyzed through close reading, coding, categorization, interpretation, and reconstruction of the problems. The findings reveal that errors were predominantly related to modeling, misconceptions of terminology, inappropriate strategy selection, and inaccuracies in mathematical notation. In addition, grammatical issues such as ambiguity, inconsistent terminology, and imprecise logical connectors were found to contribute significantly to misinterpretation and flawed mathematical reasoning. These results indicate that language and mathematical structure are closely interconnected in problem construction. Strengthening prospective teachers’ competencies in both mathematical modeling and linguistic precision is therefore essential to improve the validity and effectiveness of assessment instruments.